Paint and surface coatings : theory and practice - R LAMBOURNE
Paint composition and applications — a general introduction ; Organic film formers; Pigments for paint; Solvents, thinners, and diluents; Additives for paint; The physical chemistry of dispersion; Particle size and size measurement; The industrial paint-making process; Coatings for buildings; Automotive paints; Automotive refinish paints; General industrial paints; The painting of ships; An introduction to rheology; The rheology of paints; Mechanical properties of paints and coatings; Appearance qualities of paint — basic concepts; Specification and control of appearance; Durability testing; Computers and modelling in paint and resin formulating; Health and safety in the coatings industry